PETUNJUK ALQURAN TENTANG BELAJAR DAN PEMBELAJARAN - Munirah Munirah (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2016)
As the foundation of Islamic education, then the Quran has ranked as qath’i dalalah. while al-Hadith some are qath’i dalalah and some are zanni dalalah. Because of the case, so that Quran should be the main or first base in education, in which there are many verses found explaining about the importance of learning and teaching. The Quran also contains methods to facilitate mankind to understand the creation of God which is an essence of islamic education. This article discusses about the direction of Quran about learning and teaching, methods in Quran in learning and teaching and dialogues/discussion method. It is very interesting to be investigated because Quran has taught several very modern methods before educationist and psychologists developing it such as story method, exemplary method, practice and repetition method, ‘ibrah and mau‘idzah method, targhib and tarhib method.